P12.04 Body Mass Index: a possible PICC-related complications risk factor in neuro oncological patients. (9th September 2021) - Simonetti, G; Gaviani, P; Botturi, A; Redaelli, V; Anghileri, E; Silvani, A
Abstract: BACKGROUND: The use of central venous catheter with peripheral insertion (PICC) has increased rapidly in recent years particularly in cancer patients because they represent a stable and safe vascular access to administer irritants or vesicants therapies. However, the benefit provided may occasionally be affected by severe complications. An observational study conducted at our Institute, showed a significant increase of thromboembolic risk in neuro-oncological patients compared to general cancer population (16.3% vs 6.7% respectively). For this reason, it is essential to identify independent risk factors in order to avoid preventable harm. MATERIAL AND METHODS: Neuro-oncological patients with PICC that developed a thromboembolic event were retrospectively analyzed. We evaluated clinical data, BMI, KPS, steroid therapies and anticoagulants at the time of positioning of the PICC and at the onset of the thrombotic event. RESULTS: A total of 90 neuro-oncological patients have been analyzed. The most common histology was represented by glioblastoma, followed by anaplastic astrocytoma, primary central nervous system lymphoma, grade II glioma. 17.6% of patients were at first diagnoses, 41.6% were at the first recurrence, and the remaining patients were at the second or third recurrence. The median KPS was 90 (range 80–100), and the median ECOG was 0 (range 0–2). Overall, 14% patients developed thromboembolic events within a median time of 34.5 days (range 5–146) after PICC implantation. Among these, 64% of patients was considered overweight. No patients were on anticoagulant therapy but all were treated with a median dose of 5.5 mg of steroids (range 3, 5-12), stable between PICC insertion and onset of adverse event. CONCLUSION: 64% of patients who developed a thromboembolic event had BMI >28 at the time of PICC insertion, suggesting a possible trend towards a risk of developing PICC related thrombosis in overweight/obese patients. Other independent risk factors for PICC associated complications seems to be amount of previous chemotherapies administered: 82% of patients who developed thrombotic complications had already undergone at least one line of chemotherapy before PICC placement, suggesting this condition as a possible risk factor for the onset of the event. Also failed positioning attempts could damage vascular endothelium, contributing to the onset of thrombotic complications. An accurate anamnesis and a physical evaluation with particular attention to the presence of malnutrition could help in the in the early identification of independent risk factors that could farther negatively influence the outcome of neuro-oncological patients.